Quantifying propagation effects of climate and vegetation changes on evapotranspiration and streamflow signatures in Yarlung Tsangpo River Basin - Qi Huang; Yongqiang Zhang; Congcong Li; Ning Ma (Journal of Hydrology: Regional Studies)
Study region: Yarlung Tsangpo River basin (YTRB) went through significant increases in precipitation, temperature and leaf area index (LAI) during 1982–2018. Study focus: This study aims to investigate the propagation effects of climate and vegetation change on actual evapotranspiration (AET) and streamflow signatures with simulation experiments using an improved hydrological model that couples a diagnostic evapotranspiration module. New hydrological insights: The improved hydrological model performs well in simulating streamflow, actual evapotranspiration and most streamflow signatures in six subcatchments of upper Nuxia region of YTRB (e.g. median Nash-Sutcliffe Efficiency of daily streamflow larger than 0.72). Changes in AET and streamflow are dominated by the long-term increase in precipitation (P), followed by considerable influence from the increase in LAI and marginal influence from the increase in temperature. Increases in both P and LAI have increased AET but caused wetting and drying effects on streamflow, respectively. LAI-induced increase in transpiration and interception evaporation is partly offset by the decrease in soil evaporation, resulting in marginal changes in AET. Subsequently, changes in streamflow signatures are amplified when propagating from AET to streamflow signatures, especially for those reflecting frequency and duration. This study advanced the understanding of the propagation effect of climate and vegetation variables on AET and streamflow signatures.